Burnout Syndrome and Logotherapy: Logotherapy as Useful Conceptual Framework for Explanation and Prevention of Burnout - Riethof, Norbert; Bob, Petr (Frontiers in Psychiatry, 2019)
Burnout syndrome is a state of total exhaustion related to work conditions and stress from work. Recent findings suggest that logotherapy and the concepts of existential meaning and life fulfilment could provide useful framework for explaining and potentially preventing burnout. This review article summarizes and reflects current knowledge concerning relation between burnout syndrome and existential vacuum as a potential correlate. It also explores the risks of burnout and the need of better definition of this condition including more precise diagnostic criteria and internationally recognized measurement tools. Intensified research of relations between burnout and loss of existential meaning could help with future prevention and intervention design.